Rebuttal to “(2786) Proposal to change the conserved type of Ipomoea, nom. cons. (Convolvulaceae)” - Muñoz-Rodríguez, P; Wood, JRI; Wells, T; Carruthers, T; Sumadijaya, A; Scotland, RW (Wiley, 2023)
A rebuttal to the proposal to change the conserved type of Ipomoea is presented. We argue the proposal is unnecessary and has no basis in evidence or precedent that justifies its approval.